Impacts of eutrophication on microbial community structure in sediment, seawater, and phyllosphere of seagrass ecosystems - Deng, Wenchao; Chen, Shunyang; Chen, Shiquan; Xing, Bingpeng; Chan, Zhuhua; Zhang, Yao; Chen, Bin; Chen, Guangcheng (Frontiers in Microbiology, 2024)
Introduction: Seagrass-associated microbial communities play a crucial role in the growth and health of seagrasses. However, like seagrass meadows, seagrass-associated microbial communities are often affected by eutrophication. It remains unclear how eutrophication influences the composition and function of microbial communities associated with different parts of seagrass. Methods: We employed prokaryotic 16S rRNA gene high-throughput sequencing combining microbial community structure analysis and co-occurrence network analysis to investigate variances in microbial community compositions, potential functions and complexities across sediment, seagrass leaves, and seawater within different eutrophic areas of two adjacent seagrass meadows on Hainan Island, China. Results: Our results indicated that microbial diversity on seagrass leaves was significantly lower than in sediment but significantly higher than in seawater. Both sediment and phyllosphere microbial diversity showed no significant difference between the highly eutrophic and less eutrophic sites in each lagoon. However, sediment microbial diversity was higher in the more eutrophic lagoon, while phyllosphere microbial diversity was higher in the less eutrophic lagoon. Heavy eutrophication increased the relative abundance of phyllosphere microorganisms potentially involved in anaerobic metabolic processes, while reducing those responsible for beneficial functions like denitrification. The main factor affecting microbial diversity was organic carbon in seawater and seidment, with high organic carbon levels leading to decreased microbial diversity. The co-occurrence network analysis revealed that heavy eutrophication notably reduced the complexity and internal connections of the phyllosphere microbial community in comparison to the sediment and seawater microbial communities. Furthermore, ternary analysis demonstrated that heavy eutrophication diminished the external connections of the phyllosphere microbial community with the sediment and seawater microbial communities. Conclusion: The pronounced decrease in biodiversity and complexity of the phyllosphere microbial community under eutrophic conditions can lead to greater microbial functional loss, exacerbating seagrass decline. This study emphasizes the significance of phyllosphere microbial communities compared to sediment microbial communities in the conservation and restoration of seagrass meadows under eutrophic conditions.